Migration predictive theory in sustaining local talents cost housing / Nur Zainie Abd Hamid … [et al.] - Abd Hamid, Nur Zainie; Hassan, Prof. Madya Dr. Narehan; Ahmad, Siti Nurul Akma; Azizam, Nor Azmaniza (Division of Research, Industrial Linkages and Alumni, UiTM Cawangan Melaka, 2013)
The government of Malaysia has taken a major move to introduce the Economic Transformation Programs (ETP) with the purpose to turn Malaysia into a high-income nation economy by the year 2020. The greatest concern is the quality of human capital, especially in the healthcare industry where one pertinent problem faced by the government is the brain drain where local professionals choose to work abroad for better opportunities and job prospects. One fundamental profession that experiences the brain drain phenomenon is nursing. Based on prior studies, the need factors of migration among local nurses include individual, situational, social and structural factors are believed to impact the actual behavior of nurses' migration. Therefore, the improvised Migration Predictive Theory is designed to reverse the scenario of brain drain, specifically in the healthcare industry in order to study the influence of these need factors with the intention to migrate among medical professionals in Malaysia. It is believed that the theory will assist the Malaysian government as well as employers by exploring and identifying the underlying reasons of brain drain in ensuring that the talent pool meets the industry's demand, while at the same time foster the aspiration of the government to enhance the National Key Economic Areas (NKEAS) in becoming a high-income nation.